Copper Speciation for Natural Water by On-site Sample Treatment/Solid-phase Extraction/Inductively Coupled Plasma Mass Spectrometry - YABUTANI, Tomoki; KISHIBE, Shingo; KAMIMURA, Miki; NOZOE, Kosuke; YAMADA, Yohei; TAKAYANAGI, Toshio (Analytical Sciences, 2018)
Herein, we determined the contents of Cu(I), Cu(II), and hydrophobic Cu in natural water using on-site sample treatment, solid-phase extraction (SPE), and inductively coupled plasma mass spectrometry (ICP-MS) analysis. To prevent Cu species changes in the sampling, filtering and preconditioning steps were performed in a closed system using plastic syringes and a disposable membrane filter. Bathocuproin disulfonate (BCS) and ethylenediaminetetraacetic acid (EDTA) were selected as a Cu(I)-selective complexing agent and a Cu(II) masking agent, respectively, whereas ascorbic acid (AA) was used to reduce Cu(II) to Cu(I). Pre-conditioned samples were passed through a hydrophobic SPE column, and the retained Cu species were eluted with ethanol. Subsequently, the eluate was concentrated, and the residue was re-dissolved in 2 M HNO3 and subjected to ICP-MS analysis. No artificial changes of Cu(I) and Cu(II) species were observed at any time, with the analytical detection limit of total Cu and the blank value equaling 0.0008 and 0.0025 μg kg−1, respectively. The developed method was applied to real estuarine, riverine, and seawater samples collected in Tokushima prefecture, Japan.